Characterization of microelectrode array of dielectrophoretic microfluidic device - Md Yunus, Nurul Amziah; Zainal Abidin, Zurina; Abdul Halin, Izhal (OMICS International, 2016)
This paper presents the characterization of angled microelectrode array as dielectrophoretic microfluidic device for the continuous flow-through separation of particles. The operation of the device is demonstrated using samples of colloidal latex beads of 1 μm and 2 μm in diameter sizes, achieving 100% particle deflection with operating voltage as low as 10V and frequency as minimum as 1 MHz. This characterization is essential for dielectrophoretic separation to get the specific suggestion for each type of particle behavior via its own deflection throughout the arrays of the angled microelectrode. The paper also exhibits and discusses the detail of the theoretical background of the separation method; the structure of the device and also the result obtained that is achievable by choice of voltage and frequency.